2020
DOI: 10.3389/fendo.2020.00110
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Supplementation in Patients With Chronic Heart Failure: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: The effect of testosterone supplementation in patients with chronic heart failure (CHF) remains uncertain.Methods: A meta-analysis of randomized controlled trials (RCTs) was performed. RCTs that evaluate the chronic effect of testosterone supplementation on exercise capacity and cardiac function in CHF were identified via searching of PubMed, Embase, and the Cochrane's Library databases. Heterogeneity was evaluated by the Cochrane's Q test and I 2 statistics. A fixed-effect model was used if the he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
(88 reference statements)
0
14
0
1
Order By: Relevance
“…A 2012 meta‐analysis of randomized controlled trials strengthened the evidence of a beneficial effect of T treatment on exercise capacity and oxygen consumption in patients with CHF 164 . However, a more recent meta‐analysis showed that TRT did not improve the exercise capacity, cardiac function, quality of life, or clinical outcome of patients with CHF 165 . Taken together, current EAA guidelines recommend against the use of TRT in patients with severe CHF given the risk of polycythemia and VTE in a frail population 33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2012 meta‐analysis of randomized controlled trials strengthened the evidence of a beneficial effect of T treatment on exercise capacity and oxygen consumption in patients with CHF 164 . However, a more recent meta‐analysis showed that TRT did not improve the exercise capacity, cardiac function, quality of life, or clinical outcome of patients with CHF 165 . Taken together, current EAA guidelines recommend against the use of TRT in patients with severe CHF given the risk of polycythemia and VTE in a frail population 33 …”
Section: Methodsmentioning
confidence: 99%
“…164 However, a more recent meta-analysis showed that TRT did not improve the exercise capacity, cardiac function, quality of life, or clinical outcome of patients with CHF. 165 Taken together, current EAA guidelines recommend against the use of TRT in patients with severe CHF given the risk of polycythemia and VTE in a frail population. 33 Impaired skeletal muscle function and muscle atrophy are features of CHF that could be related to the state of chronic inflammation and insulin resistance characterizing these patients.…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…In the absence of pathologic hypogonadism, clinical studies of safety for testosterone treatment for cardiovascular events [including heart failure ( 74 ) or venous thromboembolism ( 75 , 76 )] are reported as either observational cohorts ( 75 , 77 81 ) or meta-analyses of short-term placebo-controlled randomized clinical trials ( 74 , 77 , 82 90 ). The former lack cogency due to the intractable confounding of cardiovascular disease mechanisms with numerous risk factors having comparable or greater influence than testosterone as well as the inability of observational data alone to justify interventional treatment.…”
Section: Safetymentioning
confidence: 99%
“…Opposite conclusions were, however, reported in a updated meta-analysis showing that in FH patients, testosterone supplementation within a physiological dose-range does not improve exercise tolerance (shuttle walk test or the six-minute walk test), cardiac function, quality of life, or clinical outcome. Of note, a subgroup analysis highlighted that subjects who had reached testosterone levels ≥ 25 nmol/L benefitted the most in terms of improved exercise capacity, as evaluated by shuttle walk test or the six-minute walk test [ 138 ].…”
Section: Testosterone Replacement Therapy and Cardiovascular Outcomesmentioning
confidence: 99%